2019
DOI: 10.37358/mp.20.2.5357
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study on the Behavior of Dyneema� HB26 Composite in Compression

Abstract: In the last decades as the need for high economical and technical efficiency items/applications became acute, lightweight, high strength and low-cost materials development and investigation emerged as a logical and promising course of action. With high potential for both military and civil sector, the ultra-high molecular weight polyethylene (UHMWPE) is considered a new class of material. Among this class, the Dyneema� HB26 composite is of most interest for the present study. The present paper focuses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…In this regard, for a better understanding of materials behavior, during the experimental tests (mechanical testing, ultrasonic testing), different types and configurations of samples and measurement tools have been tested (simple/bilayer/multilayer configurations, force or pressure transducers, videospeed cameras, scanning electron microscopy, computed tomography etc. ), in static, dynamic or impulsive regime, corroborated with numerical simulation, in order to obtain valid outcomes and results that can be extrapolated to large-scale experiments and applications [13,[20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, for a better understanding of materials behavior, during the experimental tests (mechanical testing, ultrasonic testing), different types and configurations of samples and measurement tools have been tested (simple/bilayer/multilayer configurations, force or pressure transducers, videospeed cameras, scanning electron microscopy, computed tomography etc. ), in static, dynamic or impulsive regime, corroborated with numerical simulation, in order to obtain valid outcomes and results that can be extrapolated to large-scale experiments and applications [13,[20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The possibility to evaluate the behavior of polyurea in different configurations and for different loadings was investigated through numerical simulations with materials models available in computational codes, being obtained results similar to the real ones [11,13,25,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Significant examples are hyperelastic materials [ 9 , 10 ], metal foams [ 11 , 12 , 13 ] and sandwich structures [ 14 ]. Detonation wave deflection: systems that deflect the blast away from the structure they are protecting, such as V-shells [ 15 , 16 , 17 ]. Shock wavefront braking: structures (perforated plates or a 3D architecture) designed to disrupt the shock wave front, placed between the detonation wave source and the target [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Detonation wave deflection: systems that deflect the blast away from the structure they are protecting, such as V-shells [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al [ 31 ] conducted dynamic compression tests on a woven glass‐fiber‐reinforced polymer composite and obtained a dynamic constitutive model based on the modified ZWT viscoelastic model. Bucur et al [ 32 ] studied the mechanical behavior of Dyneema® HB26 composite under static and dynamic out‐of‐plane compression. The results showed that the proposed constitutive model proves good correlation with Dyneema® HB26 mechanical behavior under compression loading.…”
Section: Introductionmentioning
confidence: 99%